2018
DOI: 10.4314/sokjvs.v16i1.13
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of infectious bursal disease virus antibodies in some species of poultry in Maiduguri, Nigeria

Abstract: This study was aimed at determining the antibodies of IBDV in some poultry species in Maiduguri, Nigeria. A total of 944 serum samples were collected from village chickens, broilers, layers, ducks, turkeys and geese in Maiduguri and tested for IBDV antibodies using inzyme linked Immunosorbent assay (ELISA) and a seroprevalence of 46.6% was recorded. The species distribution showed that 33.4% of local chickens (134/401), 67.3% of layers (35/52), 50.8% of broilers (159/313), 60.6% of turkeys (77/127), 65.5% of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
5
2
Order By: Relevance
“…This is slightly lower compared to what was recorded in the southwestern part of Nigeria (82.7%) (Emikpe et al, 2010), and that of 84% from Sokoto (Mungadi et al, 2015), and 82.95% from Plateau state (Ijoma et al,2020) this could be due to high level of poultry farming in southwestern part of Nigeria and more of backyard and indigenous chicken farming in Sokoto and Plateau . However, the finding is comparably higher than the 26.6% reported by Shettima et al, (2016). The reason for this might be associated with an increase in the activity of IBV among chickens and birds in the study area and also the sample size as the total samples analyzed by shettima was 188 compared to 360 samples used for this study.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…This is slightly lower compared to what was recorded in the southwestern part of Nigeria (82.7%) (Emikpe et al, 2010), and that of 84% from Sokoto (Mungadi et al, 2015), and 82.95% from Plateau state (Ijoma et al,2020) this could be due to high level of poultry farming in southwestern part of Nigeria and more of backyard and indigenous chicken farming in Sokoto and Plateau . However, the finding is comparably higher than the 26.6% reported by Shettima et al, (2016). The reason for this might be associated with an increase in the activity of IBV among chickens and birds in the study area and also the sample size as the total samples analyzed by shettima was 188 compared to 360 samples used for this study.…”
Section: Discussioncontrasting
confidence: 55%
“…The sample size for the sero-survey study was calculated using the formula by Thrusfield (2005) at 95% confidence interval level, 26.6% prevalence gotten by Shettima et al (2016) in surveillance carried out in Bornu state was used for this study. N = Z 2 pq ------d 2 Where: n = sample size Z appropriate value for the standard normal deviate for the desired confidence = 1.96 P = prevalence (26.6 % prevalence for infectious bronchitis obtained by shettima et al, 2016).…”
Section: Sample Size Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…E. coli infection in broilers usually opened a gate for secondary infection with other microorganisms through lowering the bird’s resistance causing severe illness and deaths in birds. Colibacillosis usually characterized by septicemia in acute stage resulting in death and pericarditis, airsacculitis, and perihepatitis in the subacute stage [ 43 ]. E. coli infection was clearly known to contribute marked gross and microscopic bursal lesions causing bursal atrophy that subsequently resulted in transient humeral immunosuppression [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, an overall prevalence of 66.9% was reported in Western Oromia, Ethiopia [ 38 ], whereas a high seroprevalence of 76% was reported in backyard chickens in the Amman area [ 39 ]. In contrast, other studies have suggested a relatively lower prevalence, such as 33.4% reported in Maiduguri, Nigeria [ 40 ]; 30.6% in Sudan [ 41 ]; and 34% in Pakistan using the agar gel immunodiffusion assay (AGID) test [ 42 ]. The disparity in our findings might be due to the differences in the testing methods used.…”
Section: Discussionmentioning
confidence: 99%